The environmental case for the high-speed train in the UK: examining the London–Manchester route - Miyoshi, Chikage; Givoni, Moshe (Taylor and Francis, 2013)
This article investigates the potential for environmental benefit from the introduction of the High Speed Train (HST) on the London–Manchester route in the UK, focusing on carbon dioxide (CO2) emissions. The lifecycle carbon emission of HST is assessed, and its sensitivity to demand changes is analyzed for several scenarios. Based on the UK Government demand assumptions, the analysis shows relatively limited potential for reduction in CO2 emissions. In 2033, overall CO2 reduction due to HST operation on the route is estimated at 100,000 tCO2 per annum, which is less than 0.1% of the total UK domestic transport emissions in 2007.
Keywords: carbon dioxide emissions; carbon intensity; electricity generation mix; high-speed train; life cycle assessment